2008
DOI: 10.1517/14656560802519845
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cystitis: bladder pain and beyond

Abstract: Background: Interstitial cystitis is characterized by over 6 months of chronic pain, pressure and discomfort felt in the lower pelvis or bladder. It is often relieved with voiding, along with daytime frequency and nocturia in the absence of a urinary tract infection. Interstitial cystitis occurs primarily in females including adolescents and its diagnosis is still one of exclusion. It is now recognized as a serious medical condition associated with significant disability. Objective: The aim of this paper was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 158 publications
0
27
0
Order By: Relevance
“…8,9 IC is now recognized as a serious medical condition associated with significant disability. 10 Sleep disturbance in patients with IC is considered directly related to bladder functioning. 11 Research concerning natural history and quality of life among IC patients has shown that self-reported sleep disturbance is common 12,13 and affects more than 80% of IC patients.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 IC is now recognized as a serious medical condition associated with significant disability. 10 Sleep disturbance in patients with IC is considered directly related to bladder functioning. 11 Research concerning natural history and quality of life among IC patients has shown that self-reported sleep disturbance is common 12,13 and affects more than 80% of IC patients.…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of pathogenetic mechanisms have been postulated ranging from neuroinflammatory to autoimmune or possibly infectious or toxic agents, but an inflammatory component is commonly thought to be involved. 4 Epithelial damage has often been invoked: the mucinous layer of the healthy bladder is often compromised in patients with BPS/IC, as well as in some animal models. 5,6 An initiating event (toxin) may lead to increased urothelial permeability, which in turn leads to nerve sensitization and possibly up-regulation of neurotransmitter release (tachykinins, glutamate, calcitonin gene-related peptide).…”
mentioning
confidence: 99%
“…Interstitial cystitis or painful bladder syndrome is an idiopathic disease, presenting with bladder pain and urinary frequency or urgency (Kelada and Jones 2007). The bladder pain accompanying interstitial cystitis is regional and chronic and spreads over the lower pelvic and suprapubic area and mimics neuropathic pain (Theoharides et al 2008). In isolated rat urinary bladder, H 2 S stimulates capsaicin-sensitive primary afferent neurons and produces contractile responses (Patacchini et al 2004).…”
Section: Bladder Painmentioning
confidence: 99%